2006
DOI: 10.1515/znc-2006-1-222
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genetic Variation among Hibiscus Species (Malvaceae) Using RAPD Markers

Abstract: Germplasm identification and characterization is an important link between the conservation and utilization of plant genetic resources. Traditionally, species or cultivars identification has relied on morphological characters like growth habit or floral morphology like flower colour and other characteristics of the plant. Studies were undertaken for identification and determination of genetic variation within the two species of Hibiscus and 16 varieties of Hibiscus rosa-sinensis L. through random amplified pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Thus, additional markers for identification may be useful and have been developed in several organisms. Most of them are specific DNA or RNA sequences obtained by different techniques (Li et al 2002;Randig et al 2004;Barik et al 2006;Vargas et al 2005;Bianchi et al 2004). Speciesmarker bands in native and SDS-PAGE gel electrophoresis of soluble proteins were described in fish by Hasnain et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional markers for identification may be useful and have been developed in several organisms. Most of them are specific DNA or RNA sequences obtained by different techniques (Li et al 2002;Randig et al 2004;Barik et al 2006;Vargas et al 2005;Bianchi et al 2004). Speciesmarker bands in native and SDS-PAGE gel electrophoresis of soluble proteins were described in fish by Hasnain et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Neighbour-joining tree of 126 individuals of petunia (coloured by taxon), constructed based on a matrix of microsatellite alleles shared among individuals (Turchetto et al 2015). Barik et al (2006) also found the genetic variation within the two species of Hibiscus and 16 varieties of Hibiscus rosa-sinensis L. through random amplified polymorphic (RAPD) markers. However, cluster analysis indicated that 16 varieties and two species formed one cluster.…”
Section: Figmentioning
confidence: 95%
“…Both RAPD and IS-SR marker, based on PCR techniques have proven to be a reliable, easy to generate, inexpensive and versatile set of marker that rely on repeatable amplification of DNA se-quence using single primers. The RAPD and ISSR markers can be used in the study of the genetic variability of species or natural populations and in the identification of genotypes [7][8][9][10][11][12][13][14]. In this communication, we report the feasibility of PCR-based DNA (RAPD and ISSR) marker for phylogeny study and identification for conservation of Phyllanthus species.…”
Section: Introductionmentioning
confidence: 99%